The Solve-RD Solvathons as a pan-European interdisciplinary collaboration to diagnose patients with rare disease - Yépez, Vicente; Demidov, German; Ellwanger, Kornelia; Laurie, Steven; Luknárová, Rebeka; Joseph Maran, Midhuna Immaculate; Hentrich, Thomas; Sagath, Lydia; van der Sanden, Bart; Astuti, Galuh; Neveling, Kornelia; Batlle-Masó, Laura; et al. (Nature genetics, 2025)
Despite advances in genomic diagnostics, the majority of individuals with rare diseases remain without a confirmed genetic diagnosis. The rapid emergence of advanced omics technologies, such as long-read genome sequencing, optical genome mapping and multiomic profiling, has improved diagnostic yield but also substantially increased analytical and interpretational complexity. Addressing this complexity requires systematic multidisciplinary collaboration, as recently demonstrated by targeted diagnostic workshops. Here, we highlight the experience of the Solve-RD consortium, a pan-European initiative, in implementing four structured workshops, termed ‘Solvathons’, as a regular and effective component of its operational workflow. We provide actionable insights, best practices and lessons learned for successful data integration, expert training and scalable collaborative diagnostics within large research consortia.